Ideologi Kesamarataan antara Lelaki dan Wanita Berdasarkan Perspektif Naqli dan Neurosains : The Ideology of Equality between Men and Women Based on the Perspectives of Naql and Neuroscience - Mohd, Robiatul Adawiyah; Mohd Ghazali, Norzulaili; Noh, Nor Azila; Mukhtar, Firdaus (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The strife for equality between men and women is an ideology that has long been propagated by feminists. Among the equalities being propagated is women’s ability to use common sense at par with men to the extent that they proclaim some of the Qur’anic verses and hadiths related to women as irrelevant. To them, the prescribed texts seem to degrade women. To dispute this ideology, the classic and also the present scholars of Islam presented arguments to disprove the notion by the feminists. However, in rebutting this ideology, arguments based on the neuroscience perspective are yet to be discovered. Therefore, this article will incorporate the arguments from the perspectives of naqli (the Qur’an and Hadith) and neuroscience in terms of the different aspects of male and female brain function. This study employs qualitative methods through content analysis of Qur’anic texts, ahadith and neuroscience facts. The findings show that there are differences in the structure and function of the male and female brains. Consequently, there is no such ideology of equality due to the differences in the structure and function of the male and female brains that correspond to their roles and complement each other. It is hoped that this finding will enhance the public understanding that Islam glorifies women and that their obligations as caliphs on this earth are in accordance with their nature, either from the biological, psychological and emotional regards.